Effects of wearing a cooling vest during the warm-up on 10-km run performance - Stannard, A. B.; Brandenburg, J. P.; Pitney, W. A.; Lukaszuk, J. M. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine whether wearing a cooling vest during an active warm-up would improve the 10-km time trial (TT) performance of endurance runners. Seven male runners completed 3 10-km TTs (1 familiarization and 2 experimental) on a treadmill after a 30-minute warm-up. During the warm-up of the experimental TTs, runners wore either a t-shirt (control [C]) or a cooling vest (V), the order of which was randomized. No differences were found between the C and V conditions for the 10-km TT times (2,533 ± 144 and 2,543 ± 149 seconds, respectively) (p = 0.746) or any of the 2-km split times. Heart rate (HR) at the start of the TT equaled 90 ± 17 b/min for C and 94 ± 16 b/min for V. The HR peaked at 184 ± 20 b/min in C and 181 ± 19 b/min in V. At the start of the TT Tc was 37.65 ± .72°C in C and 37.29 ± .73°C in V (p = 0.067). In C, Tc gradually increased until 39.34 ± 0.43°C while in V is reached 39.18 ± 0.72°C (p = 0.621). Although rating of perceived exertion (RPE) and Thermal sensation (TS) increased during both experimental TTs, there were no differences between V and C. Findings suggest wearing a cooling vest during a warm-up does not improve 10-km performance. The use of cooling vests during the warm-up did not produce any physiological (HR and Tc) or psychological (RPE and TS) benefit, perhaps accounting for the lack of improvement.